Nana in the city [book with audioplayer] - Castillo, Lauren (Findaway World, LLC, 2020)
A young boy is frightened by how busy and noisy the city is when he goes there to visit his Nana, but she makes him a fancy red cape that keeps him from being scared as she shows him how wonderful a place it is.